KEPEMIMPINAN IDEAL UNTUK GENERASI MILLENIALS: A FIELD STUDY - Kusumadewi, Ni Wayan Duarsih; Darma, Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.11.TAHUN.2021, 2021)
The purpose of this study is to describe and explain the ideal leadership strategy desired by the millennial generation in the current workplace in the new normal era situation. The data analysis technique in this research is descriptive qualitative, in which the data is obtained from the results of interviews, observations and documentation. The results of this study are good leadership and what is desired by the current millennial generation is in the form of fair leadership, adaptive to have integrity, initiative when making decisions, assertive, have good relationships and communication with employees, able to accept criticism and have good knowledge and experience. as well as being able to provide incentives when there are new programs within the company.